Regulation of lipoprotein lipase translation by epinephrine in 3T3-L1 cells. Importance of the 3' untranslated region. - A Yukht; R C Davis; J M Ong; G Ranganathan; P A Kern (The Journal of Clinical Investigation, 1995)
Lipoprotein lipase (LPL) is a central enzyme in lipoprotein metabolism and is in part responsible for adipocyte lipid accumulation. Catecholamines are known to decrease the activity of LPL in adipocytes, and we have previously demonstrated that this inhibition occurs posttranscriptionally, with a prominent inhibition of LPL translation. To better characterize the inhibition of LPL translation, 3T3-L1 cells were differentiated into adipocytes, and exposed to epinephrine. Epinephrine induced a dose-dependent decrease in LPL synthesis using [35S]methionine incorporation, with no change in LPL mRNA levels, demonstrating translational regulation of LPL in this cell line. The poly A-enriched RNA from epinephrine-treated cells was translated well in vitro, and there was no difference in the polysome profiles from control and epinephrine-treated cells, suggesting that epinephrine did not affect mRNA editing, and did not induce an inhibition of translation initiation. To obtain evidence for the presence of an inhibitory factor, a cytoplasmic extract from control, and epinephrine-treated adipocytes was human. When compared to the control cell extract, the epinephrine-treated cell extract sharply inhibited LPL translation in vitro, yet had no effect on the translation of other mRNAs. Epinephrine-treated cells had fourfold more of this inhibitor activity than control cells, and this translation inhibition was partially reversed by heat treatment. To determine what region of the LPL mRNA was involved in the translation inhibition, different LPL constructs were synthesized. The inhibitory effect of the epinephrine-treated cell extract was dependent on the presence of the first 40 nucleotides of the 3' (untranslated region UTR) (nucleotides 1599-1638), whereas deletion of the 5' UTR and other areas of the 3' UTR had no effect on translation inhibition. When a sense RNA strand corresponding to this region was added to the in vitro translation reaction, it restored translation towards normal, suggesting that the sense strand was competing for a transacting binding protein. Thus, epinephrine-treated adipocytes produced a transacting factor, probably a protein, that interacted with a region on the LPL mRNA between nucleotides 1599 and 1638, resulting in an inhibition of translation. These studies add new insight into the hormonal regulation of LPL. Images